Renewable energy consumption, trade openness and agricultural productivity in Africa - Iwegbu, Onyebuchi (2024)
This study examines the relationship between renewable energy consumption, trade openness and agricultural productivity in Africa. Specifically, the study examines the intensity of the type of renewable energy consumed in Africa; investigates the effect of renewable energy consumption on agricultural productivity in Africa and analyse the effect of trade openness on agricultural productivity via the consumption of renewable energy in Africa. In achieving this, the System Generalized Methods of Moments (SYSGMM) estimation technique is employed while also checking the robustness of the result using the cross section augmented distributed lag model estimation technique. The result from the study shows that hydro and low carbon type of renewable energy accounts for over 90% of the renewable energy consumed in Africa between 2000 and 2020. Also, the result from the study shows that there is a positive and significant impact of renewable energy consumption on agricultural productivity in Africa. Trade openness and agricultural productivity have a positive relationship as trade openness facilitates the importation of machines that uses renewable energy in the agricultural value chain system. Thus, encouraging policy actions and the intensification of the use of renewable energy improves agricultural productivity in Africa. At regional level and in the long run, renewable energy consumption has a positive and significant effect on agricultural productivity only in Central and Southern region of Africa. Also, at the regional level, trade globalization has a positive and significant impact on agricultural productivity by enhancing the deployment of machines that uses renewable energy in the agricultural productivity in Central and Southern regions of Africa in the long run, and in the Eastern and Western regions of Africa in the short run. The use of renewable energy in the agricultural value-added space requires the deployment of new and innovative equipment which are mostly imported into Africa just like the processing and irrigation equipment; and these guarantees increase in agricultural productivity and efficiency. There is the need for respective governments of African economies and international development partners to provide finance for farmers which encouragesimportation of renewable energy enabled agricultural machineries used for processing, irrigation, packaging, refrigerating, transport system, storage, and handling value chains to guarantee improved agricultural productivity. Keywords: Agricultural Productivity; Renewable Energy Consumption; Trade Openness.